2017
DOI: 10.1302/1863-2548.11.160008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D insufficiency in children with forearm fractures

Abstract: PurposeThis study aimed to determine whether children with distal radius impaction fractures have increased prevalence of 25-hydroxyvitamin D (25(OH) D) insufficiency compared with healthy controls.Patients and MethodsThis is a prospective controlled study. The 30 children who were diagnosed with forearm fracture at the orthopaedic emergency clinic were included in the study and 30 healthy children from the routine paediatric outpatient unit were included as the control group. Peripheric venous 25(OH) D, calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…32 The consequence of this process is a poor bone quality which in turn leads to a higher fracture risk at the end of winter. 33,34 While this effect might be more subtle in countries like Israel where winters are mild and the UVB exposure is consistently higher, 30,35 in areas that have long and dark winters children might begin their spring sports activities with more vulnerable bones. 3,16,33 During spring outdoor activities become frequent as the weather becomes friendlier.…”
Section: Discussionmentioning
confidence: 99%
“…32 The consequence of this process is a poor bone quality which in turn leads to a higher fracture risk at the end of winter. 33,34 While this effect might be more subtle in countries like Israel where winters are mild and the UVB exposure is consistently higher, 30,35 in areas that have long and dark winters children might begin their spring sports activities with more vulnerable bones. 3,16,33 During spring outdoor activities become frequent as the weather becomes friendlier.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, the patient group showed lower bone mineral density and was more likely to be vitamin D deficient (47.1% vs. 40.8%). Likewise, Saglam et al compared the vitamin D levels of 30 fracture patients with 30 controls and found that vitamin D levels were significantly lower in patients with forearm fractures (14.5 ng/mL vs. 21.3 ng/mL, p =0.002) [ 23 ]. In contrast, Minkowitz et al failed to show a significant difference between vitamin D levels and the risk of fracture in a study that compared 369 fracture patients with 662 nonfracture controls aged 18 years and younger and find no differences in vitamin D status (27.5 ± 8.9 ng/mL vs. 27.4 ± 9.1 ng/mL) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The background of repeated fractures in healthy children is insufficiently understood. Studies have shown associations between childhood fracture and higher levels of socioeconomic deprivation [ 4 ], high levels of vigorous exercise [ 5 ], high body mass index (BMI) and overweight status [ 6 ], vitamin D insufficiency [ 7 ], low calcium intakes, and physical abuse [ 8 ]. Children who fracture repeatedly may also have especially fragile skeletons, or they may be “accident-prone,” or they may occur due to sport or physical activity that actually improves bone strength during growth [ 3 ].…”
Section: Introductionmentioning
confidence: 99%